THEORETICAL INVESTIGATION OF TWO-MASS ACOUSTIC SYSTEM WITH RESILIENT ELEMENT - I. V. Lugovoy (Наука и техника, 2012)
The paper presents a calculation of two-mass vibrating system, which has a resilient element in an energy  storage device. Graphical results of calculations in the form of sampling analogue-frequency characteristics are given in the paper.